Verbal memory in breast cancer patients treated with chemotherapy with doxorubicin and cyclophosphamide. (29th August 2017) - Andryszak, P.; Wiłkość, M.; Żurawski, B.; Izdebski, P.
Abstract : Memory is one of the crucial human cognitive functions, and deficits in memory processes may lead to difficulties in everyday functioning. The aim of this study was to analyse the effect of anthracycline‐based adjuvant chemotherapy (AC) used in breast cancer treatment on verbal memory and learning. We also evaluated the relationship between verbal memory and psychological, somatic and socio‐demographic factors. The study was carried out on a group of 31 women with early breast cancer treated with adjuvant chemotherapy and 30 healthy controls. The patients underwent neuropsychological assessment using the Rey Auditory Verbal Learning Test at three time points: before chemotherapy, mid‐chemotherapy and post‐chemotherapy. The examination in the controls was conducted at the same time intervals. We found an association between AC‐schema chemotherapy and deficits in delayed memory. A deterioration in performance after treatment was observed in 19% of patients. The results showed no deterioration of immediate memory or the verbal learning process. Moreover, a positive relationship was shown between the level of education, physical fitness and the functioning of verbal memory. The results of the study also indicate that age and hormonal status are factors that may increase the possibility of deficits in verbal memory after AC‐schema chemotherapy.